A Wax Barrier to Simulate Bone Resorption for Pre-Clinical Laboratory Models of Cemented Total Hip Replacements - Cherukuri, Anjuli R (2010)
Pre-clinical tests are often performed to screen new implant designs, surgical techniques and cement formulations. In this work, we developed a technique to simulate the cement-bone morphology found with postmortem retrieved cemented hip replacements. With this technique, a soy wax barrier is created along the endosteal surface of the bone, prior to cementing of the femoral component. This approach was applied to six fresh frozen human cadaver femora and the resulting cement-bone morphology and micromotion following application of torsional loads were measured on a transverse section of each bone. The contact fraction between cement and bone for the wax barrier specimens (6.4±5.7%, range: 0.5 – 15%) was similar to that found in post-mortem retrievals (10.5±10.3%, range: 0.4–32.5%). Micro-motions at the cement-bone interface for the wax barrier specimens (0.5±1.06 mm, range: 0.005–2.66) were similar, but on average larger, than those found with postmortem retrievals (0.092±0.22mm, range: 0.002–0.73). The use of a wax barrier coating technique could improve experimental pre-clinical tests because it produces a cement-bone interface similar to those of functioning cemented components obtained following in vivo service.